CERPENIS SUFISTIK: MOHAMMAD FUDOLI ZAINI - Maman S. Mahayana (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article describes Mohammad Fudoli Zaini’s work by analyzingits content. His work figured world-in as a counter to literature paradigm world-outside. The basic of world-in comes from the conscience, based on obedience and religiosity. His world-in paradigm rooted on Jalal al-Din Rumi, an outstanding Persian Sufi who said that world-in might be better on changing oneself and its society.